2011
DOI: 10.1158/1078-0432.ccr-10-3019
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Circulating Tumor Cell Counts Significantly Enhance a Prognostic Score for Patients Participating in Phase I Oncology Trials

Abstract: Background: High circulating tumor cell (CTC) counts are associated with poor prognosis in several cancers. Enrollment of patients on phase I oncology trials requires a careful assessment of the potential risks and benefits. Many patients enrolled on such trials using established eligibility criteria have a short life expectancy and are less likely to benefit from trial participation. We hypothesized that the incorporation of CTC counts might improve patient selection for phase I trials.Methods: This retrospec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Bidard and coworkers demonstrated detection of a single CTC in 7.5 ml of blood was associated with poor OS and development of metastasis in breast cancer patients [24]. Olmos et al showed that higher CTC count as a continuous variable was correlated with patient death in Phase I trials with various tumor types [25]. We separated the patients with detectable CTC into 2 groups (1-3 and >3 CTC) based on their CTC number at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bidard and coworkers demonstrated detection of a single CTC in 7.5 ml of blood was associated with poor OS and development of metastasis in breast cancer patients [24]. Olmos et al showed that higher CTC count as a continuous variable was correlated with patient death in Phase I trials with various tumor types [25]. We separated the patients with detectable CTC into 2 groups (1-3 and >3 CTC) based on their CTC number at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, selection of patients with no CTC or a lower CTC count may reduce the patient loss and warrant a proper evaluation of investigational immunotherapeutic agents in early phase clinical trials. It has been reported that incorporation of the CTC count could improve the performance of prognostic score used for patient selection for phase I trials [25]. …”
Section: Discussionmentioning
confidence: 99%
“…It is likely to be difficult to improve on this level prediction using basic clinical and laboratory parameters. This suggests that the integration of more sophisticated parameters reflecting other dimensions than tumour burden and its consequences, such as tumour growth dynamics (Gomez-Roca et al , 2011) or the presence of circulating tumour cells (Olmos et al , 2011), may need to be incorporated if the predictive value of models is to improve.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several models predictive of early death in this context have been proposed (Janisch et al , 1994; Yamamoto et al , 1999; Bachelot et al , 2000; Verweij, 2000; Han et al , 2003; Arkenau et al , 2008a, 2008b, 2009; Penel et al , 2008, 2009, 2010; Wheler et al , 2009; Olmos et al , 2011). Arkenau et al (2008a, 2008b) developed a score based on overall survival, which then was validated by logistic regression analysis for prediction of 90-day survival.…”
mentioning
confidence: 99%
“…Both CTCs and DTCs may have prognostic potential as markers for survival and metastasis in patients with BC [12,[22][23][24][29][30][31][32][33][34][35][36][37][38][39] or prostate cancer (PC) [40][41][42][43] and for survival in colorectal cancer (CRC) [44,45]. Persistence of DTCs after radical prostatectomy was an independent predictor of disease recurrence in patients with PC, suggesting that DTCs also may be clinically significant in this patient population.…”
Section: Prognostic Value Of Circulating and Dis-seminated Tumor Cellmentioning
confidence: 99%